Trade-offs from a family perspective: considerations in choosing between omalizumab and complementary alternative medicine for pediatric severe asthma - Chen, Hang; Xu, Yan; Qiu, Jian-Li; Guan, Zhi-Wei; Wei, Mu-Mu; Zhang, Yi; Xu, Ji-Xiang; Cui, Hong-Tao (Frontiers in Pharmacology, 2025)
The management of pediatric severe asthma poses significant challenges for families. When faced with the choice between targeted biologics like omalizumab and widely used complementary alternative medicine (CAM), families navigate a complex decision-making process influenced by multiple factors. This review adopts a family-centered perspective to systematically analyze key factors influencing this trade-off: treatment goals (extending beyond clinical metrics to focus on quality of life), risk perception (shaped by subjective constructs and lacking direct evidence for comparative risk assessments), treatment burden (often overlooked hidden costs), and the current state of shared decision-making (SDM). Analysis reveals that family decision-making is a multidimensional construct shaped by four core elements: value systems, lived experiences, risk perception patterns, and tolerance for treatment burden. Notably, the significant gap in risk perception evidence leads to subjective risk assessments dominating decisions, particularly in CAM choices. Treatment burden, a critical hidden cost, is often marginalized in decisions, hindering effective SDM. Health equity further profoundly impacts choices. The conclusion emphasizes the need for clinical practice to shift toward family-centered care by addressing real-world needs, routinely evaluating treatment burden, optimizing risk communication, overcoming SDM barriers, and promoting health equity. Future research must fill evidence gaps in risk perception, develop SDM tools, and address culturally diverse family needs.